An Approach to the Islamization of Social and Behavioral Sciences (American Journal of Islam and Society, 1989)
AbstractIn this paper I have tried to argue that the two widely used paradigmsof Individualism in Western social science, and Collectivism in Soviet socialscience, are not appropriate for Islamic social science on account of thesecularism (disregard of revelation) of the former and the "scientific atheism"of the latter. I have funher tried to argue that the hypothetico-deductive andempirical methodology (often called logical positivism) of natural and physicalscience is not appropriate for social and behavioral science in general, andIslamic social behavioral science in particular. It would be more fitting toregard the various disciplines of social and behavioral science as moral sciencesin order to incorporate the values, morals, and purposes of society in theorybuildingand hypothesis-formation. Accordingly, I am arguing in favor ofa moral explanation of human behavior and social processes. A moralexplanation is one which seeks to discover the causes (immediate antecedents)as well as reasons (including motives and intentions) behind human behaviorwith the greater responsibility for the explanation resting with the latter.A paradigm, conceptual framework, or what is called grand theory isessential for the formulation of theories in various fields of social and behavioralsciences, on the one hand, and for guiding empirical research. on the other.Western social science and Soviet social science have their respectiveparadigms. The immediate need of Islamic social science is to construct adistinguishable paradigm of its own. I have tried to formulate a list of theunderlying concepts of such a possible paradigm, conceptual framework,or grand theory, but not such a theory per se.Finally, I have made the suggestion that, inasmuch as the understandingof human behavior is our goal, the social and behavioral scientist could enhancethe understanding of human and social phenomena by trying to understandhis/her own motives, behavior, and actions ...